Effects of medication knowledge on medication adherence among hypertensive patients at Matero level one hospital, Lusaka city, Zambia: a cross sectional study - Kampamba, Martin; Abanur, Farhiyyah; Hikaambo, Christabel Nang’andu; Mudenda, Steward; Saini, Kennedy; Kaonga, Patrick (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Medication adherence is the mainstay to good treatment outcomes. Failure to adhere to medication in hypertensive patients may lead to considerable deterioration of the disease resulting in increased costs of healthcare and mortality. Knowledge about the name of the drug, indications and side effects may enhance medication adherence. Therefore, the aim of this study was to assess effects of medication knowledge on medication adherence among hypertensive patients. Methods: This was a cross-sectional study that involved 120 hypertensive patients. A structured questionnaire was used to collect data on demographic characteristics. Adherence was assessed using the 8-item Morisky medication adherence scale while patient’s medication knowledge was assessed using a 7-item scale. Multiple logistic regression was used to assess factors associated with medication adherence. Results: The mean age of participants was 59 years (SD±14.9) and 10 (8.3%), 42 (35%) and 68 (56.7%) had adequate, average and poor medication knowledge respectively. The prevalence of adherence in this study was 37.5%. In multivariable logistic regression analysis, uncontrolled blood pressure (BP) (AOR: 0.38, CI: 0.16-0.90) was associated with lower likelihood of adhering to medication. Conclusions: The adherence level to treatment was low and medication knowledge of hypertensive patients was generally poor. Uncontrolled BP was associated with non-adherence. Patients with uncontrolled hypertension should be given health education and counselling regarding their condition to improve medication adherence.